Chico's Sizing - Mullet,Kathy; Burns,Leslie D (2018)
The businessproblem associated with Chico’s development of a unique sizing system is speculative only and not based on publicly available and/or documented information from Chico’s. The authors do not intend to illustrate either effective or ineffective handling of a situation.
Keywords: Design Program